Leadership Agility and Digital Quotient Influence on Employee Engagement: A Case of PT X and Pinrumah.com - Ririn Fitaloka; Bima Sugarai; Andi Randirga Arung Perkasa; Nopriadi Saputra (Bina Nusantara University, 2020)
The research aimed to determine whether leadership (leadership agility) and digital intelligence (digital quotient) have an influence on employee engagement. The data collection method was conducted by distributing questionnaires to employees, which obtained a sample of 150 people in pharmaceutical companies and Pinrumah.com. The analysis method was multiple regression analysis using IBM SPSS Statistics 20 software as data processing. The results show that both leadership agility and digital quotient have significant effects on employee engagement.